(untitled) (Bangladesh Journal of Pharmacology, 2015)
Spectrophotometric method of arsenic estimation in nails has four steps: a) washing of nails, b) digestion of nails, c) arsenic generation, and finally d) reading absorbance using spectrophotometer. Although the method is a cheapest one, widely used and effective, it is time consuming, laborious and need caution while using four acids. Video Clips Nail wash: 3.2 min Digestion of nail: 7.0 min Arsine generation: 10.0 min Reading absorbance: 1.2 min